The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.3748/wjg.v12.i28.4578
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effect of Diammonium Glycyrrhizinate in a rat model of ulcerative colitis

Abstract: Diammonium Glycyrrhizinate could reduce inflammatory injury in a rat model of ulcerative colitis. This may occur via suppression of NF-kappaB, TNF-alpha and ICAM-1 in colonic mucosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
46
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 15 publications
2
46
0
1
Order By: Relevance
“…It was also reported that GA scavenges free radical species by increasing superoxide dismutase activity in atherosclerotic and hypercholesterolemic rabbits [15] . More recently, studies have suggested that GA and its derivatives may abolish TNF-α-induced leukocyte adhesion and extravasation in the in vivo microcirculation, and attenuate the elevation of ICAM-1 expression in rat models of hepatic injury and colic ulceration [16][17][18] . However, the effect of GA on ICAM-1 expression in cytokine-activated vascular endothelial cells is not clearly defined.…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported that GA scavenges free radical species by increasing superoxide dismutase activity in atherosclerotic and hypercholesterolemic rabbits [15] . More recently, studies have suggested that GA and its derivatives may abolish TNF-α-induced leukocyte adhesion and extravasation in the in vivo microcirculation, and attenuate the elevation of ICAM-1 expression in rat models of hepatic injury and colic ulceration [16][17][18] . However, the effect of GA on ICAM-1 expression in cytokine-activated vascular endothelial cells is not clearly defined.…”
Section: Introductionmentioning
confidence: 99%
“…DG possesses a high antiinflammatory effect, which protects the hepatic cell membrane, and ameliorates liver function (Xu et al 2009;Yuan et al 2006). It would undoubtedly be beneficial to understand the mechanisms of the hepatoprotective effect of this herbal ingredient in metabolic regulation.…”
mentioning
confidence: 99%
“…Clinically, DG is widely used in the therapy of chronic hepatitis for its effects of inhibiting inflammatory reactions and ischemia-reperfusion injury. These effects have been demonstrated to be beneficial in rat models of ulcerative colitis and cerebral ischemia reperfusion (7,8). The present study focused on its effect on random skin flap survival in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, DG is widely administered to patients with chronic hepatitis and human immunodeficiency virus infection for its anti-inflammatory, anti-viral and hepatoprotective effects (5,6). A previous study in a model of ulcerative colitis indicated that DG was able to reduce inflammatory injury via suppression of nuclear factor κ-light-chain-enhancer of activated B cells (NF-κB), tumor necrosis factor-α and intercellular adhesion molecule 1, which are thought to promote inflammatory injury (7). Furthermore, it was found that DG had neuroprotective potential against ischemia-reperfusion injury in a model of focal cerebral ischemic-reperfusion injury, and this effect was also likely associated with the anti-inflammatory function of DG according to a previous study (8).…”
Section: Introductionmentioning
confidence: 99%